(untitled) (Actual Problems of Mind, 2017)
This paper presents a review of some key ideas of Wittgenstein, in particular, the problem of their interpretation is discussed in order to expand the boundaries of understanding and explanation. This is an attempt to actualize certain systematic aspects of Wittgenstein’s research program.